Artificial Intelligence dalam Bimbingan dan Konseling: Tinjauan Sistematis tentang Peluang, Efektivitas, dan Isu Etis - Wikan Galuh Widyarto; Dony Apriatama; Dian Ari Widyastuti; Hardi Prasetiawan; Dzinnun Hadi; Rizky Andana Pohan (Universitas Palangka Raya, 2026)
The mental health of adolescents and young adults in educational settings has become increasingly urgent, while conventional psychological support services are not always able to meet these needs in a rapid, flexible, and broad manner. This study aimed to synthesize the opportunities for utilizing artificial intelligence (AI) in guidance and counseling, examine the effectiveness of AI- and digital-based services, and map the ethical issues associated with their implementation. This study employed a systematic literature review (SLR) approach following the PRISMA 2020 guidelines to review articles published between 2021 and 2025. The initial search identified 87 articles. After the stages of identification, screening, and eligibility assessment, 19 articles were selected and analyzed using narrative thematic synthesis. The findings revealed three major themes: (1) the potential of AI to expand access, enhance personalization, and improve service efficiency; (2) the effectiveness of digital services such as cybercounseling, chatbots, and hybrid AI-human models in reducing certain psychological problems; and (3) the prominence of ethical issues, including data privacy, algorithmic bias, information security, and counselors’ professional readiness. This study concludes that AI should be positioned as a strategic partner that supports humanistic counseling services rather than as a full replacement for human counselors.